Good stories overwrite creativity: the three eras of city competition - Koudela, Pál (Creativity Studies, 2024)
Today cities in national and global competition focus on creativity. Although the creative city concept was invented by Gunnar Törnqvist in 1983, today the dominant concept is creative class articulated by Richard Florida in 2004. Cities are engaged to strengthen their social and cultural environment in the direction indicated in the works by Törnqvist, Peter Hall, Charles Landry, and Florida, and take effort to embed their fame as creative cities to their city branding. This let them communicate a creative image and develop an emotional bond to this image among larger social groups of tourists, employees and beyond. Consequently, their position in competition is improving. The emergence of creativity basically changed the characteristics of city competition since the turn of the millennia, cities – stakeholders in particular – focused on investment and infrastructure development beforehand. As the concept of the creative city already stabilized itself in worldwide city development and branding a new turn might come, and the market of good stories is emerging in city communication which can dim or even overwrite the importance of creativity. While good stories were always part of marketing, and contributed to city planning since the 1980s, their growing importance in city branding can reach a hypothetical point where a new market level develops, and a narrative turn occurs. In such cases, cities themselves carry good stories and the represented virtual reality creates a new market, where creativity will be only one among other stories. In this study we sketch up the three eras of branding in city competition, focusing on the emerging and fading role of creativity.